Deficiency of the microprocessor component DGCR8 impairs macrophage growth and unleashes IFN-dependent gene expression in response to mycobacteria - Killy, Barbara; Bodendorfer, B.; Pracht, Katharina; Jäck, Hans-Martin; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

DGCR8 deficiency impairs macrophage growth and unleashes the interferon response to mycobacteria - Killy, Barbara; Bodendorfer, Barbara; Mages, Jörg; Ritter, Kristina; Schreiber, Jonathan; Hölscher, Christoph; Pracht, Katharina; Ekici, Arif Bülent; Jäck, Hans-Martin; Lang, Roland (Life Science Alliance, 2021)
The mycobacterial cell wall glycolipid trehalose-6,6-dimycolate (TDM) activates macrophages through the C-type lectin receptor MINCLE. Regulation of innate immune cells relies on miRNAs, which may be exploited by mycobacteria to survive and replicate in macrophages. Here, we have used macrophages deficient in the microprocessor component DGCR8 to investigate the impact of miRNA on the response to TDM. Deletion of DGCR8 in bone marrow progenitors reduced macrophage yield, but did not block macrophage differentiation. DGCR8-deficient macrophages showed reduced constitutive and TDM-inducible miRNA expression. RNAseq analysis revealed that they accumulated primary miRNA transcripts and displayed a modest type I IFN signature at baseline. Stimulation with TDM in the absence of DGCR8 induced overshooting expression of IFNβ and IFN-induced genes, which was blocked by antibodies to type I IFN. In contrast, signaling and transcriptional responses to recombinant IFNβ were unaltered. Infection with live Mycobacterium bovis Bacille Calmette-Guerin replicated the enhanced IFN response. Together, our results reveal an essential role for DGCR8 in curbing IFNβ expression macrophage reprogramming by mycobacteria.
CRIS-Team Scopus Importer:2021-04-16

Dual role of the mycobacterial cord factor TDM in cross-regulation of macrophage responses to IFN gamma - Killy, Barbara; Huber, Angelika; Ekici, Arif Bülent; Wirtz, Stefan; Dalpke, A.; Lang, Roland (2017)
EVALuna2:33888

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Mycobacterial Cord Factor Reprograms the Macrophage Response to IFN-γ towards Enhanced Inflammation yet Impaired Antigen Presentation and Expression of GBP1 - Huber, Alexandra; Killy, Barbara; Grummel, Nadine; Bodendorfer, Barbara; Paul, Sushmita; Wiesmann, Veit; Naschberger, Elisabeth; Zimmer, Jana; Wirtz, Stefan; Schleicher, Ulrike; Vera, Julio; Ekici, Arif Bülent; et al. (Journal of Immunology, 2020)
Mycobacteria survive in macrophages despite triggering pattern recognition receptors and T cell-derived IFN-γ production. Mycobacterial cord factor trehalose-6,6-dimycolate (TDM) binds the C-type lectin receptor MINCLE and induces inflammatory gene expression. However, the impact of TDM on IFN-γ-induced macrophage activation is not known. In this study, we have investigated the cross-regulation of the mouse macrophage transcriptome by IFN-γ and by TDM or its synthetic analogue trehalose-6,6-dibehenate (TDB). As expected, IFN-γ induced genes involved in Ag presentation and antimicrobial defense. Transcriptional programs induced by TDM and TDB were highly similar but clearly distinct from the response to IFN-γ. The glycolipids enhanced expression of a subset of IFN-γ-induced genes associated with inflammation. In contrast, TDM/TDB exerted delayed inhibition of IFN-γ-induced genes, including pattern recognition receptors, MHC class II genes, and IFN-γ-induced GTPases, with antimicrobial function. TDM downregulated MHC class II cell surface expression and impaired T cell activation by peptide-pulsed macrophages. Inhibition of the IFN-γ-induced GTPase GBP1 occurred at the level of transcription by a partially MINCLE-dependent mechanism that may target IRF1 activity. Although activation of STAT1 was unaltered, deletion of Socs1 relieved inhibition of GBP1 expression by TDM. Nonnuclear Socs1 was sufficient for inhibition, suggesting a noncanonical, cytoplasmic mechanism. Taken together, unbiased analysis of transcriptional reprogramming revealed a significant degree of negative regulation of IFN-γ-induced Ag presentation and antimicrobial gene expression by the mycobacterial cord factor that may contribute to mycobacterial persistence.
CRIS-Team Scopus Importer:2020-09-18

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16